Birth-Rates in Rich Districts and in Poor (Quarterly Journal of Economics, 1899)
Journal Article Birth-Rates in Rich Districts and in Poor Get access The Quarterly Journal of Economics, Volume 14, Issue 1, November 1899, Pages 125–129, https://doi.org/10.1093/qje/14.1.125 Published: 01 November 1899